Simulation Based Exploration of SKC Block Cipher AlgorithmAn Exploration of Monetary Based Approach (MBA) in Peer-to-peer system Network: A Review - Gupta, Durba Das; Faiyaz Ahamad,; Khan, Mohammad Zunnun (International Journal of Computer Sciences and Engineering, 2021)
The major concept of the Monetary Based Approach (MBA) network uses the Label Switch Path (LSP) technique that pro- vides high performance in packet delivery without routing table lookup. Nevertheless, it needs more overhead to rebuild a new path when occurring link failure in the MBA network. MBA (Monetary Based Approach) networks are currently evolving towards a universal and convergent network, capable of flowing multiservice traffic (voice, data and video) over the same IP based infrastructure. Quality of Service (QoS) is more and more becoming a necessity for emerging applications carried by MBA networks. This fact stimulates service providers to improve network planning techniques to adequately provide network resources and overcome all failures. The paper presents typical network failures, which cause path recovery in MBA networks and experimental results of network failures, when MBA is used.